DESIGN AND DEVELOPMENT OF AN ETAXATION SYSTEM - Ernest E., Onuiri; Fikayo, Faroun; Ogheneovo, Erhinyeme; Ayodeji, Jegede (European Scientific Journal, ESJ, 2015)
Tax is any form charge levied on a person or an institution by a governing body or its equivalent such that defaulted payment is punishable by law. The imposition of taxes and the institution of taxing is as old as civilization itself cutting across religion, race and continental borders. Prompt tax payment and reduced tax evasion is always a primary objective of the government in most civilizations that exist today. The issue of tax evasion has proven to be a difficult practice to curb even in nations with a proper database of its citizenry and the current mode of tax payment is redundant and hectic as ascertained through a survey of our case study. Some of the challenges governmental bodies have to overcome in order to encourage the prompt payment of taxes and effectively reduce evasion includes, developing convenient payment methods and having proper records keeping systems. This paper is a concise summary of how the continuous development of computing science and its wide spread ability to be deployed to solve a wide range of problems can be geared towards the development of an electronic taxation system to assist government bodies with convenient tax collection and record keeping. The waterfall methodology was selected for system development. Goals to be achieved by the system are instant access, improved productivity through efficient utilization of resources, database creation and records management, simplification of operations, reduced processing time, user friendliness, portability and flexibility for further enhancement. The E-taxation is not a new system, but a rather local solution to a problem with global purview. This system looks at how tax payment can be encouraged through simplification and increased efficiency in payment processing.